Analisis Pengaruh Biaya Pemasaran dan Biaya Administasi dan Umum terhadap Laba Bersih Pada Perusahaan Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia Periode 2022-2023 - Annisa, Mutiara Lusiana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to analyze the influence of marketing costs and administrative and general costs on net profit in food and beverage companies listed on the Indonesia Stock Exchange during the 2022-2023 period. The data used in this research is secondary data obtained from financial reports and company annual reports. The research sample consists of companies that have positive current-year profits. The analytical method used is multiple linear regression analysis to determine the relationship between the independent variables (marketing costs and administrative and general costs) and the dependent variable (net profit). The research results show that marketing costs have a positive and significant influence on net profit. Efficient and strategic spending in marketing activities has been proven to increase sales volume and company income. Additionally, administrative and general costs also show a significant influence on net profit. Effective management of administrative and general costs, such as controlling employee salaries, office costs, and other operational expenses, can help companies reduce costs and increase profit margins. This research emphasizes the importance of managing marketing costs and administrative and general costs in achieving optimal financial performance. Companies in the food and beverage sector need to balance spending on these two types of costs to maximize net profit.